2015
DOI: 10.1177/1932296815593094
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Physiological Factors Affecting Glucose Sensor Function in Vivo

Abstract: For implantable sensors to become a more viable option for continuous glucose monitoring strategies, they must be able to persist in vivo for periods longer than the 3-to 7-day window that is the current industry standard. Recent studies have attributed such limited performance to tissue reactions resulting from implantation. While in vivo biocompatibility studies have provided much in the way of understanding histology surrounding an implanted sensor, little is known about how each constituent of the foreign … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…We have also demonstrated that MΦ can act as metabolic sinks for glucose by depleting local glucose levels in vitro and in vivo and causing anomalous glucose sensor reading (Klueh et al 2014a). These and other studies support our general hypotheses that MΦ recruitment and activation can directly decrease glucose sensor function and CGM performance in vivo (Klueh et al 2010a; Klueh et al 2015; Novak and Reichert 2015; Novak et al 2014). Since the recruitment and accumulation of inflammatory leukocytes to injured tissue is dependent on the local generation of leukocyte chemotactic factors (LCF), we chose to investigate the role of monocyte/macrophage LCF in controlling MΦ recruitment into sensor implantation sites and sensor function (Figure 1).…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…We have also demonstrated that MΦ can act as metabolic sinks for glucose by depleting local glucose levels in vitro and in vivo and causing anomalous glucose sensor reading (Klueh et al 2014a). These and other studies support our general hypotheses that MΦ recruitment and activation can directly decrease glucose sensor function and CGM performance in vivo (Klueh et al 2010a; Klueh et al 2015; Novak and Reichert 2015; Novak et al 2014). Since the recruitment and accumulation of inflammatory leukocytes to injured tissue is dependent on the local generation of leukocyte chemotactic factors (LCF), we chose to investigate the role of monocyte/macrophage LCF in controlling MΦ recruitment into sensor implantation sites and sensor function (Figure 1).…”
Section: Introductionsupporting
confidence: 89%
“…Implantable glucose sensors used in CGM are known to induce foreign body reactions characterized by the accumulation of macrophages (MΦ) and formation of FBGC at the sensor-tissue interface. Recently, the sensor literature underscored that the presence of MΦ at sites of sensor implantation reduces sensor performance including CGM (Klueh et al 2014a; Klueh et al 2014b; Novak and Reichert 2015; Novak et al 2014). Moreover, it is known that mice deficient in CCL2 (MCP-1) experience minimal fibrotic reactions in response to an implant (Castro et al 2014; Moore et al 2015; Skokos et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Newly implanted CGMs are exposed to a complex milieu of blood, interstitial fluid, and infiltrating inflammatory cells. The consequences of these exposures have been carefully addressed by previous works (19). The current study was conducted using time points after the transient period of dynamic healing because the duration of this healing process is short and the response is heterogenous, dependent on the vascularization of the precise site of insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the research concerning the effects of the foreign body response on CGM accuracy has focused on cellular and biochemical effects that interfere with detection of glucose by glucose oxidase ( 15 17 ). However, foreign body capsules have been shown to slow the diffusion of interstitial solutes ( 18 ), and this effect has been postulated to delay the arrival of glucose in the CGM microenvironment ( 19 ). That said, the magnitude and functional importance of this effect within the time frames characteristic of commercial CGM usage are currently unknown, and the high rate of glucose diffusion observed in vivo may render foreign body response–induced delays negligible relative to those caused by smoothing algorithms and genuine interstitial latency, among others.…”
Section: Introductionmentioning
confidence: 99%
“…FBGC formation causes increased implant destruction as well as cytokine secretion to promote the deposition of a fibrotic capsule . Fibrotic encapsulation of implants increases the diffusion barrier and can result in implant failure . Attempts to modulate the FBR have taken various forms, but some of the most effective have been coating the implants in drug eluting materials.…”
Section: Resultsmentioning
confidence: 99%